Business Development Service Provider Organizations in Micro Entrepreneurship Development in Western Hill, Nepal - Karki, Bir Bahadur (Janapriya Journal of Interdisciplinary Studies, 2017)
Business Development Service Providers Organization (BDSPO) play vital role specially in Micro Entrepreneurship Development (MED) sectors. BDSPO provides various types of services such as skill oriented training, facilitates to establish enterprises, identify sources of raw materials and other equipments, establish market link etc. Major Activities of the BDSPOs includes social mobilization of potential micro entrepreneurs, formation of Micro Enterprise Group (MEG) formation, House-Hold (HH) survey and participants selection, conduct Entrepreneurship Development Training (EDT) programmes, provides skill training and appropriate technology support, help to establish marketing linkage and product promotion, need assessment of entrepreneurs, identify and provide scale up activities, facilitates micro credit accessibilities, facilitates to formation of cooperatives and product association, facilitation of construction of new Common Facility Centers (CFCs) and examine as well as assess the uses of existing technology. The main objective of MEDEP is “improve the socio economic status hardcore poor and non hard core poor people through Micro Enterprise”. On the response of the question of how do entrepreneur rate the business supportive policies of the other agencies like BDSPOs, 32.5percent entrepreneurs felt that the business supportive policies of the other agencies supportive. By 35.6 percent respondents felt the supportive policies of the other agencies is less supportive. The researches try to examine of the change in self-confidence before participation in EDP and after EDP. Paired t-test between effectiveness before participation in EDP and after EDP has been conducted. This shows a statistically significant influence of EDP on confidence level. Janapriya Journal of Interdisciplinary Studies, Vol. 5 (December 2016), page: 14-26